Risk of Latent Tuberculosis Reactivation After Hematopoietic cell Transplantation. (28th March 2019) - Cheng, Matthew P; Kusztos, Amanda E; Bold, Tyler D; Ho, Vincent T; Glotzbecker, Brett E; Hsieh, Candace; Baker, Meghan A; Baden, Lindsey R; Hammond, Sarah P; Marty, Francisco M
Abstract: There were no cases of tuberculosis in a cohort of 2531 patients who underwent hematopoietic cell transplantation from 2010 to 2015 after 7323 person-years of follow up (95% confidence interval [CI], 0.0–0.05 cases/100 person-years), including 29 (1.15%) patients with untreated latent tuberculosis after 89 person-years of follow-up (95% CI, 0.0–4.06 cases/100 person-years).